Direct Correlation between Adsorption Energetics and Nuclear Spin Relaxation in a Liquid‐saturated Catalyst Material. Issue 19 (21st September 2018) - Robinson, Neil; Robertson, Christopher; Gladden, Lynn F.; Jenkins, Stephen J.; D'Agostino, Carmine
Abstract: The front cover artwork is provided by the groups of Stephen J. Jenkins and Lynn F. Gladden at the University of Cambridge, and Carmine D'Agostino at the University of Manchester. The image shows alcohol adsorption at a silica catalyst support surface, the energetics of which may be investigated through nuclear spin relaxation measurements. Read the full text of the Article at10.1002/cphc.201800513 . Abstract : "Nuclear spin relaxation measurements provide insight into the surface dynamics of adsorbed liquids within optically opaque mesoporous media, such as heterogeneous catalysts…" This and more about the story behind the front cover can be found in the Article at10.1002/cphc.201800513 .